The Clinical Features and Pathophysiology of Acute Radiation Dermatitis in Patients Receiving Tomotherapy - Lee, Ji Hyun; Kay, Chul Seung; Maeng, Lee So; Oh, Se Jeong; Lee, An Hi; Lee, Jeong Deuk; Han, Chi Wha; Cho, Sang Hyun (Annals of dermatology, 2009)
Radiation therapy (RT) including tomotherapy has been widely used to treat primary tumors, as well as to alleviate the symptoms of metastatic cancers. The primary purpose of this study was to examine the characteristics of the clinical features and pathophysiological mechanisms associated with acute radiation dermatitis in cancer patients that received tomotherapy, and compare the results to patients treated by conventional radiation therapy. The study population consisted of 11 patients that were referred to the dermatology department because of radiation dermatitis after receiving tomotherapy; all patients were evaluated for clinical severity. The patients were assessed and identified using the National Cancer Institute Common Toxicity Criteria version (CTC) 3.0. We performed biopsies of the skin lesions that were examined for apoptosis using the terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labelling (TUNEL) assay and stained immunohistochemically with monoclonal antibodies to CD8, CD4 and TGF-beta. As a positive control, patients with radiation dermatitis treated with conventional radiation therapy were also studied. THE RESULTS OF THE CLINICAL FEATURES OF THE SKIN OF TOMOTHERAPY PATIENTS WERE THE FOLLOWING: grade 1 (36%), grade 2 (55%) and other changes (9%). Among the population that had skin lesions due to acute radiation dermatitis, the mean number of positive cells per high power field (HPF) was the following: there were 30.50+/-7.50 TUNEL-positive cells, 34.60+/-12.50 CD8+ T cells, 5.19+/-3.17 CD4+ T cells and 9.95+/-1.33 TGF-beta positive cells measured per HPF. The mean number of positive cells per HPF for the patients that received conventional radiation therapy was: TUNLEL-positive cells in 7.5+/-1.64, CD8-, CD4- and TGF-beta-positive cells in 12.50+/-3.73, 3.16+/-1.47, 6.50+/-1.97. We found that the number of TUNEL-positive cells and CD8+ T cells were higher in the lesions of patients receiving tomotherapy compared to the lesions of the patients receiving conventional radiation therapy. These findings suggest that tomotherapy without dose modification may cause significantly more severe forms of radiation dermatitis by apoptosis and cytotoxic immune responses than conventional radiation therapy.